2022
DOI: 10.1002/eom2.12261
|View full text |Cite
|
Sign up to set email alerts
|

High‐entropy oxide: A future anode contender for lithium‐ion battery

Abstract: Revolutionary changes in energy storage technology have put forward higher requirements on next-generation anode materials for lithium-ion battery. Recently, a new class of materials with complex stoichiometric ratios, highentropy oxide (HEO), has gradually emerging into sight and embracing the prosperity. The ideal elemental adjustability and attractive synergistic effect make HEO promising to break through the integrated performance bottleneck of conventional anodes and provide new impetus for the design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 93 publications
0
31
0
Order By: Relevance
“…However, the current limited understanding of the growth mechanism of HEMs hinders the clarification of the solution mechanism of HEMs. 4 Since it is difficult to explain, this problem only through thermodynamic criteria, it is analyzed here from the perspective of synthesis dynamics. The whole synthesis process can be divided into two parts, 56 ion diffusion and nucleation, in which the speed of ion diffusion determines the subsequent nucleation growth mechanism.…”
Section: Solid-solution Mechanism Of Hems From the Point Of View Of T...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the current limited understanding of the growth mechanism of HEMs hinders the clarification of the solution mechanism of HEMs. 4 Since it is difficult to explain, this problem only through thermodynamic criteria, it is analyzed here from the perspective of synthesis dynamics. The whole synthesis process can be divided into two parts, 56 ion diffusion and nucleation, in which the speed of ion diffusion determines the subsequent nucleation growth mechanism.…”
Section: Solid-solution Mechanism Of Hems From the Point Of View Of T...mentioning
confidence: 99%
“…18 Throughout the synthesis process, thermodynamics would control the overall directions of reactions. However, drawing a complete blueprint for the synthesis of HEMs based only on such state quantities is difficult since this cannot effectively clarify the solid–solution mechanism of HEMs 4 nor predict the synthesis path of the products and their surface interface properties. Consequently, predicting the improvement of the catalytic performance of HEMs using the synthesis method is challenging.…”
Section: Supplementing Synthetic Kinetic Criteria Under the Thermodyn...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, high entropy oxides (HEOs) as a novel class of multication metal oxides have attracted intensive interest for battery applications [18][19][20][21][22][23][24] . In particular, it has been reported that micrometersized HEO particles show extraordinary long-term cycling stability at high capacity without a necessity for nanostructuring when used as anode material in LIBs 20 .…”
mentioning
confidence: 99%
“…The unexpected performance has been attributed to the randomly mixed five metal elements in a single-phase solid solution without chemical short-range order. This has been supposed to result in a high configurational entropy, stabilizing the crystal structure during lithium storage 18,20,23,24 . However, solely considering the entropy is insufficient to explain the reversibility of the conversion reaction and the high electron conductivity that is required for the long reaction path due to the large particle size.…”
mentioning
confidence: 99%